Main conceptual provisions of the creation of an electronic state register of immovable cultural heritage of Ukraine. Part 2: processes - Chabaniuk, V.; Dyshlyk, O.; Polyvach, K.; Pioro, V.; Kolimasov, I.; Nechyporenko, J. (Land Management, Cadastre and Land Monitoring, 2022)
Abstract. Part 2 describes the processes of activities for the creation of a new modern electronic State Register of Immovable Cultural Heritage (CH) of Ukraine. They are part of the methodology based on AGIS-CH1 Solutions Framework (SoFr), where AGIS-CH1 represents the first queue of the hierarchically structured Atlas GeoInformation System (AGIS). AGIS-CH generally consists of four strata: Operational (w), Application (a), Conceptual (b) and General (g). The processes in the article refer to AGIS1 aSoFr, which determines the activities "between" AGIS1 subsystems of the Application and Operational strata. The processes related to bSoFr AGIS-CH1, which determines the activities "between" AGIS-CH1 subsystems of the Conceptual and Application strata, are also mentioned.AGIS-CH1 SoFr is defined by packages and relations between them of Publications-Products-Processes-Basics-Services "petrad". Packages Products-Processes-Basics and the relations between them are called the main triad of SoFr. This triad is the basis of the main conceptual provisions 1-3. They are formulated as follows: AGIS-CH1 SoFr.Products – provision 1, AGIS-CH1 SoFr.Processes – provision 2, AGIS-CH1 SoFr.Basics – provision 3.Part 2 describes AGIS-CH1 SoFr.Processes – development and quality assurance processes of AGIS-CH1, which corresponds to the Main Conceptual Provision 2.Key words: Solutions Framework (SoFr), Atlas GeoInformation System (AGIS), State Register of Immovable Cultural Heritage, development and quality assurance processes.
Keywords: Solutions Framework (SoFr); Atlas GeoInformation System (AGIS); State Register of Immovable Cultural Heritage; development and quality assurance processes.